Purchasing Decisions and Consumer Preferences of Millennials and Zoomers at Coffee Shops - Depicha Zambustya Zamborita; Yanti Nuraeni Muflikh; Al-May Abyan Izzy Burhani (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2024)
The transformational era has given rise to a new generation that is presumed to have different preferences than the previous generation. The proliferation of coffee shops has expanded consumer alternatives for purchasing decisions. This research aims to identify and segment Millennial and Zoomer consumers based on demographic, behavioral, and psychographic characteristics in the purchase of coffee beverages at coffee shops. The research employed a non-probability sampling method, specifically judgmental sampling, with a sample size of 180 coffee shop consumers in Madiun City. The data were analyzed using descriptive statistics, independent sample t-tests, and K-means clustering. The research findings indicate that millennials and Zoomer consumers tend to be dominated by females, mostly visiting once a week for leisure and prioritizing taste quality. There are significant differences between Millennial and Zoomer consumers in terms of promotional media attributes, WiFi/power outlet availability, live music entertainment, ordering process, and payment options. Based on consumer segmentation analysis, three segments were identified: coffee enthusiasts, adventurous coffee connoisseurs, and consumers who prioritize coffee beverage quality. The managerial implications for coffee shops involve directing marketing strategies specifically towards the adventurous taste segment and emphasizing quality by prioritizing innovation and differentiation in serving high-quality coffee beverages.